ChemInform Abstract: N‐Allenyl Amides and O‐Allenyl Ethers in Enantioselective Catalysis. Issue 35 (11th August 2016) - Manoni, Elisabetta; Bandini, Marco
Abstract: Review: [recent advances in the use of such activated π‐systems in metal‐mediated and metal‐free enantioselective transformations; 32 refs.